Pendidikan Islam pada penjajahan Belanda: Antara Pembatasan dan Perlawanan - Nur Azizah; Salsa Sahlat; Idris L (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study discusses Islamic education during the Dutch colonial period by focusing on colonial policies, forms of restrictions imposed on Islamic educational institutions, and the role of Islamic education as a means of resistance among indigenous communities. During the colonial era, education did not merely function as a medium of learning, but was also used by the Dutch government as a political instrument to maintain colonial power and spread Western cultural influence. In this situation, pesantren, surau, and madrasah experienced various forms of pressure through strict supervision, limitations on religious activities, and educational regulations such as the Teacher Ordinance. This research employs a qualitative method with a library research approach by collecting data from books, academic journals, and historical documents related to Islamic education during the Dutch colonial era. The findings show that despite the colonial government's efforts to restrict the development of Islamic education, Islamic educational institutions continued to survive and develop as centers of moral, religious, and social formation within Muslim society. Pesantren functioned not only as institutions for religious learning, but also as centers for fostering patriotism and national awareness. Therefore, Islamic education during the Dutch colonial period played an important role in preserving Muslim identity while simultaneously becoming part of the resistance against colonialism in Indonesia.